Antihypertensive effects of Trichiurus lepturus myosin hydrolysate in spontaneously hypertensive rats. Issue 4 (16th April 2020) - Fu, Weiqing; Wang, Peixin; Wu, Hongqiang; Zhang, Zhigang; Zeng, Hongliang; Zhang, Yi; Zheng, Baodong; Hu, Jiamiao
Abstract : In this study, the blood pressure-lowering effects of Trichiurus lepturus myosin hydrolysate (TMH) and its possible mechanism were investigated in spontaneously hypertensive rats (SHRs). Abstract : In this study, the blood pressure-lowering effects of Trichiurus lepturus myosin hydrolysate (TMH) and its possible mechanism were investigated in spontaneously hypertensive rats (SHRs). After gavage administration of TMH for 4 h, systolic blood pressure (SBP) was significantly decreased in SHRs. Furthermore, the SBP of SHRs remained low at 1 month after daily TMH treatment at 400 mg kg −1 . Meanwhile, plasma levels of angiotensin II, bradykinin and nitric oxide in SHRs were ameliorated by TMH. Western blotting also suggested that TMH down-regulated the expression of ICAM-1 and VCAM-1, indicating a strong anti-inflammatory effect. Additionally, nitrotyrosine and collagen I were down-regulated, revealing a significant anti-oxidant effect of TMH. No obvious side effects or toxicity were observed in normal Wistar rats given TMH. Various pathogenic factors related to hypertension were improved by TMH, which may explain the underlying mechanism by which TMH synergistically reduces blood pressure.